Next-Generation Textiles - Ibrahim, Hassan (IntechOpen, 2023)
Intelligent textiles are the next generation of textiles, materials, and products designed to react quickly to changes in their surroundings. They are designed to keep us cool in hot conditions, warm in cold environments, and comfortable in our regular day-to-day activities. They are utilized for convenience, fashion, safety, and protection. They also have applications in health care and hygiene in the form of intelligent medical textiles. This book provides a comprehensive overview of these exciting new materials. Chapters discuss such topics as implantable and non-implantable applications in medical textiles, restrictions on the recycling of intelligent textiles, electronics and conductive materials in textiles, and more.